Inhaled nitric oxide in persistent pulmonary hypertension of the newborn: usage protocol in a specialized pediatric institute in Latin America - Paredes-Espinoza, Adria Patricia (2023)
The use of inhaled nitric oxide is part of the therapeutic strategies in the newborn with severe pulmonary pathology associated with pulmonary hypertension. The nitric oxide allows an improvement in oxigenation by promoting pulmonary vasodilation. As inclusion criteria we have pulmonary hypertension diagnosed by echocardiography and hypoxemic respiratory failure. Patients with left ventricular dysfunction, intracraneal hemorrhage, chromosomopathies or malformations incompatible with life are not eligible. The objective of our publication is to describe our protocol for the use of inhaled nitric oxide in pulmonary hypertension of the newborn at “Instituto Nacional del Niño-San Borja”, in Lima Perú.